2019
DOI: 10.1177/0363546519864718
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Safe Extra-articular Parameters for Cortical Button Distal Fixation During Ulnar Collateral Ligament Reconstruction

Abstract: Background: A variety of methods exist for fixation during ulnar collateral ligament (UCL) reconstruction on the ulna for the overhead throwing athlete. Current biomechanical evidence suggests that cortical button fixation may fail at a higher load and under more cycles than interference screw fixation alone, while also minimizing the risk of fracture. A safe angle for placement of this cortical button has not yet been determined. Purpose: To define a safe angle for cortical button deployment during UCL recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The pull-out force of a cancellous bone screw is an important index for predicting screw loosening and fracture block displacement. 9,11,12,21 The study of Chatzistergos et al 26 has shown that the main parameters affecting the pull-out force are the outer diameter of the screw and the fixed length inside bone, and the pull-out force is linearly related to the fixed length of the bone. The experiments of Feng et al 27 indicated bone screws with a reverse buttress thread design will significantly increase the pull-out strength.…”
Section: The Change Pattern Of Pull-out Forces Of Assbf and Adsbf For...mentioning
confidence: 99%
See 2 more Smart Citations
“…The pull-out force of a cancellous bone screw is an important index for predicting screw loosening and fracture block displacement. 9,11,12,21 The study of Chatzistergos et al 26 has shown that the main parameters affecting the pull-out force are the outer diameter of the screw and the fixed length inside bone, and the pull-out force is linearly related to the fixed length of the bone. The experiments of Feng et al 27 indicated bone screws with a reverse buttress thread design will significantly increase the pull-out strength.…”
Section: The Change Pattern Of Pull-out Forces Of Assbf and Adsbf For...mentioning
confidence: 99%
“…[5][6][7][8] Since the proximal ulna is covered with thin cortex and loose spongiosa, especially in patients with osteoporosis, problems such as screw loosening, displacement or rotation of the fracture block, and screws stripping may occur when the single or plural screws are improperly fixed. [9][10][11][12] To avoid problems with a single screw, double lag screws sometimes can be used to enhance fixation stability. However, experimental studies have shown that there is no significant difference in lateral bending stability between single-screw fixation and double-screw fixation, 13,14 and the single-screw fixation has the advantages of reducing time and costs of operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation